A comprehensive experimental and computational study of highly efficient organic NLO crystal: Anilinium -L-Tartrate. (May 2021) - Sudha, N.; Mathammal, R.; Shankar, R.; Sharon Benita, G.
Graphical abstract: Highlights: An organic salt ALT 1+ ∙Tart 1- was grown by slow evaporation method. Structural, optical and spectral studies confirm optical applications. HOMO-LUMO band gap energy of the crystal was calculated to be 6.41 eV. The MEP surface shows the sites of electrophilic and nucleophilic reactions. The first-order hyperpolarizability (β) is 10 times higher than that of urea. Abstract: In the field of nonlinear optics, the organic materials have new corners compared to inorganic materials. Aniline as well as tartrate possesses high nonlinear optical behaviour especially for second harmonic generation. Single crystals of Anilinium-L-Tartrate (ALT) salt is grown from solution growth technique. ALT crystal belongs to triclinic system with space group P1 which is basically a donor acceptor organic material. The grown crystal is subjected to characterisations such as optical, mechanical and spectral studies to propose the material for useful applications. The details of theoretical calculations of macroscopic nonlinear properties molecular orbital calculations and Hirschfield Analysis are also reported in the present work.